Safety and efficacy of high-dose rifampicin in the management of tuberculosis meningitis: Systematic review and meta-analysis - Loveness Charlie; Solomon Mequante Abay; Abraham Tesfaye; Ronald Nachipo Mlera; Samuel Mwango; Mary Goretti (International Journal of Mycobacteriology, 2021)
Background: Mycobacterium tuberculosis (TB) practically affects any part of the body, but when the brain is involved, the consequences are devastating. Tuberculous meningitis (TBM) is the most severe form of drug-susceptible TB, with an estimation of more than 100,000 new cases occurring every year and a high mortality rate globally. The treatment strategy is based on pulmonary TB (PTB) management regimens which consider rifampicin as the backbone. Optimal treatment regimens for PTB may not be the most effective option for TBM due to difference in TB drug penetration across the blood–cerebrospinal fluid barrier, hence the need for other treatment options. This study aims to review the efficacy and safety of higher doses of rifampicin (>10 mg/kg) compared to 10 mg/kg rifampicin as part of standard therapy for the treatment of TBM. Methods: A systematic review and meta-analysis was conducted to assess the efficacy and safety of high-dose rifampicin for TBM. A search was done on PubMed, Google Scholar, and Cochrane library databases without publication date limit to identify studies providing data on the use of high-dose rifampicin for the treatment of TBM. Titles and abstracts were screened for relevance by three reviewers. Two reviewers used a predefined checklist on the inclusion criteria to assess full text for their eligibility in the review. A heterogeneity test was conducted to assess the variations among study outcomes. The risk ratio (RR) with a 95% confidence interval (CI) was calculated as a measure of intervention effect. The study is registered on PROSPERO and the registration number is CRD42020212737. Results: Five Phase 2 trials with a total of 1028 participants were included in this meta-analysis. All the five trials were used to analyze safety data, which found that there was no significant increase in the risk of Grade 3–5 adverse events in high-dose rifampicin (RR = 1.05; 95% CI = 0.95–1.18). Only four of them were included for the analysis of efficacy. The findings indicated that exposure to high-dose rifampicin is not associated with a reduced risk of mortality (RR = 0.95; 95% CI = 0.78–1.16). Conclusions: It can be concluded from this meta-analysis that there is no significant relation of high-dose rifampicin with adverse events and the reduction of mortality in TBM patients. Whether in future optimized TBM treatment regimen will include high-dose rifampicin or not should be determined by a large-scale clinical trial.